An Analysis of Studentsâ€™ Need in Learning English at the Marketing Department of SMK Negeri 1 Kolaka - Hendra, Hendra (Journal of Teaching and Education, 2022)
This research was aimed to answer the problem of the researchÂ â€œWhat were the studentsâ€™ needs in the Marketing Department At SMK Negeri 1 Kolaka in learning English?â€. This research used a qualitative research design. So the data were explained in the description form. The instruments of the research were questionnaires and interview guidelines. The participants of the research were students of the Marketing Department in the second grade in SMK Negeri 1 Kolaka. The result showed the student needs, the first is for the student's necessities who were more likely to learn speaking skills, and also for the material they want is online marketing material, which means that they consider their needs in the future when they enter the world of work, another thing that students need is in their English learning was they need a material that was appropriate to their major so that what they learn in school can be applied when they are working later, while the students lack was their speaking skill and also vocabulary deficiencies. Which was where they have no space or place to use their English skills that they have learned and for the desires of students in terms of learning English, students are more likely to want to learn English is more likely to go outside and also for the learning methods used by the teacher, students are more likely to study in pairs or groups with their friends rather than study alone. Besides, students also want teachers who can become facilitators and guides in the English learning processÂ